Pandemic-Resilient Sustainable Settlement Model in Makassar City - Resky, Ninik Dwi; Arifin, Mimi; Wunas, Shirly (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
A pandemic is one of many types of disasters that must be considered in emergency response planning. Currently the Covid-19 pandemic is sweeping the world, including Indonesia, so there is increasing concern about urban settlements that have high density and vulnerability to Covid-19 because housing is one of the important factors during the pandemic. Based on this, it is deemed necessary to conduct a study on a sustainable urban settlement model that is resilient to pandemics so that it can facilitate and overcome pandemic cases that have or will occur. Resilient housing is a residential area or residence inhabited by people who are ready to face any threat, including Covid-19. The research location is a residential real estate located in the city of Makassar. This research aims to analyze the conditions of urban settlement which viewed from the ressilience toward pandemic and analyze the socio-cultural and economic conditions against vulnerability of pandemic transition to obtain a sustainable model that is resilient to the pandemic. The research method used is multiple regression, t test and f test. As a result, the most influential factor on the security of housing residents during the pandemic is supervision, while the most influential factor in increasing the transmission of Covid-19 is the vulnerability of socio-economic mix, both of which are the most dominant variables in increasing housing resilience to the pandemic. There are various control strategies with a pandemic resilient sustainable housing model, namely increasing supervision, limiting socio-economic mixing, principles of resilience and sustainability.